ANALYSIS OF THE INFLUENCE OF INTERNAL FACTORS ON PROJECT PERFORMANCE IN LOW-RISE COMMERCIAL BUILDING CONSTRUCTION PROJECTS IN TANGERANG - Ardianto Vernandes Laia; Budi Susetyo (LPPM Universitas Negeri Jakarta, 2024)
From the construction statistics data of the city of Tangerang, in 2022 the construction business field contributes 8.16 percent to the total economy of the city of Tangerang, each construction project certainly has a certain work plan and work schedule, which is so that the project can be completed as planned. The impact that causes delays in project implementation time can be accompanied by increased costs of implementing the project. This study aims to know and identify and analyze factors - factors Labor factors, material factors, equipment factors, place characteristics factors, managerial factors, planning and scheduling factors and other factors. that affects time and cost performance. Research uses SEM-PLS to determine potentially influencing factors through literature review. The results of the study found that managerial factors had a significant influence on time performance with a coefficient value of 3.962, while planning and scheduling had a significant influence with a coefficient value of 2.773. While the effect of time performance on cost increase has a significant effect of 5.465.